Decoration of MoS2 Nanopetal Stacks with Positively Charged Gold Nanoparticles for Synergistic Electrocatalytic Oxidation of Biologically Relevant Compounds. (10th November 2015) - Dolinska, Joanna; Chidambaram, Arunraj; Taleat, Zahra; Adamkiewicz, Witold; Lisowski, Wojciech; Palys, Barbara; Holdynski, Marcin; Andryszewski, Tomasz; Sashuk, Volodymyr; Rassaei, Liza; Opallo, Marcin
Graphical abstract: Abstract: Synthesis of new nanohybrid materials and exploration of their synergistic behaviours are of high importance in the field of electrocatalysis mainly for their potential applications in sensing and energy conversion. Here, MoS2 nanopetal stacks bearing partial negative charge were decorated with positively charged gold nanoparticles (with mercaptoalkylammonium functionalities of two different lengths) via droplet deposition of individual components on indium tin oxide. The higher coverage density of gold nanoparticles with shorter alkyl chain functionalities on MoS2 nanopetal stacks was evidenced by scanning electron microscopy and X-ray photoelectron spectroscopy. IR spectra of these hybrid materials is typical for gold nanoparticles. Synergistic electrocatalytic properties of these hybrid materials towards the oxidation of biologically relevant compounds such as cysteine, glutathione and glucose were demonstrated by significant shifts of the onset oxidation potentials and higher current densities.